Integrating Handgrip Exercise and Lavender Aromatherapy into Nursing Care for Pain Management in Peptic Ulcer Patients with Melena - Salma Dena; Muhamad Zulfatul A'la; Rondhianto Rondhianto; Mohammad Shodikin (KHD Production, 2026)
Peptic ulcer disease frequently precipitates acute pain and gastrointestinal hemorrhage, yet conventional analgesic use remains constrained by bleeding risks and mucosal irritation. This study evaluated the clinical effectiveness of integrating handgrip exercise and lavender aromatherapy into nursing care for pain reduction in a patient presenting with melena secondary to peptic ulcer disease. Employing a prospective single-patient case design, the intervention was administered over three consecutive days using standardized nursing protocols. Pain intensity was quantified using the Numerical Rating Scale (NRS) immediately before and after each 30-minute session, with continuous hemodynamic and clinical monitoring. Results demonstrated a progressive attenuation of pain intensity, with NRS scores declining from 7 to 4 across the intervention period, concurrent with improved physiological stability and enhanced patient-reported comfort. These outcomes suggest that the combined modalities operate through complementary neurophysiological pathways, leveraging diffuse noxious inhibitory controls and limbic-mediated autonomic regulation to modulate both sensory and affective pain dimensions. The findings underscore the clinical feasibility, safety, and analgesic potential of structured, nurse-delivered nonpharmacological interventions in acute gastrointestinal settings. Systematic integration of such multimodal protocols into routine nursing practice offers a viable strategy for optimizing pain management while minimizing pharmacological adverse effects. Further randomized controlled investigations are recommended to establish dose-response parameters, validate long-term efficacy, and develop standardized implementation guidelines for broader clinical adoption.